Overexpression of partner of numb induces asymmetric distribution of the PI4P 5-Kinase Skittles in mitotic sensory organ precursor cells in Drosophila. - Perdigoto, C.N.; Gervais, L.; Overstreet, E.; Fischer, J.; Guichet, A.; Schweisguth, F. (PLoS ONE, 2008)
Unequal segregation of cell fate determinants at mitosis is a conserved mechanism whereby cell fate diversity can be generated during development. In Drosophila, each sensory organ precursor cell (SOP) divides asymmetrically to produce an anterior pIIb and a posterior pIIa cell. The Par6-aPKC complex localizes at the posterior pole of dividing SOPs and directs the actin-dependent localization of the cell fate determinants Numb, Partner of Numb (Pon) and Neuralized at the opposite pole. The plasma membrane lipid phosphatidylinositol (4,5)-bisphosphate (PIP2) regulates the plasma membrane localization and activity of various proteins, including several actin regulators, thereby modulating actin-based processes. Here, we have examined the distribution of PIP2 and of the PIP2-producing kinase Skittles (Sktl) in mitotic SOPs. Our analysis indicates that both Sktl and PIP2 reporters are uniformly distributed in mitotic SOPs. In the course of this study, we have observed that overexpression of full-length Pon or its localization domain (LD) fused to the Red Fluorescent Protein (RFP::Pon(LD)) results in asymmetric distribution of Sktl and PIP2 reporters in dividing SOPs. Our observation that Pon overexpression alters polar protein distribution is relevant because RFP::Pon(LD) is often used as a polarity marker in dividing progenitors.